2014
DOI: 10.1149/2.0321410jes
|View full text |Cite
|
Sign up to set email alerts
|

Ultra High-Precision Studies of Degradation Mechanisms in Aged LiCoO2/Graphite Li-Ion Cells

Abstract: Twenty LiCoO 2 /Graphite cells with ages between 0 and 12 years having different cycling histories but identical chemistry and construction were obtained from Medtronic Inc. These cells presented a unique opportunity to learn about aging mechanisms in Liion cells. The cells were studied using the ultra-high precision chargers (UHPC) at Dalhousie University, electrochemical impedance spectroscopy (EIS) and differential voltage versus capacity (dV/dQ vs Q) measurements. Even after 12 years of operation at 37 • C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 23 publications
4
38
0
Order By: Relevance
“…The time dependence was set to be proportional to the square root of time as reported by several researchers. [86][87][88][89][90][91] The cycle number dependence can come from the SEI repair at the surface of the Si-alloy particles due to the volume changes upon lithiation and delithiation. In these fits, the possibility of lithium plating was ignored since no plating was observed in cells cycled at C/2.…”
Section: Impedance Of Individual Electrodes Of Lco/si-alloy:graphite mentioning
confidence: 99%
“…The time dependence was set to be proportional to the square root of time as reported by several researchers. [86][87][88][89][90][91] The cycle number dependence can come from the SEI repair at the surface of the Si-alloy particles due to the volume changes upon lithiation and delithiation. In these fits, the possibility of lithium plating was ignored since no plating was observed in cells cycled at C/2.…”
Section: Impedance Of Individual Electrodes Of Lco/si-alloy:graphite mentioning
confidence: 99%
“…Finally, some of the Li is also lost irreversibly to side reactions at either electrode with reduced and oxidized electrolyte species on the anode (solid electrolyte interphase, SEI) and cathode (cathode electrolyte interphase, CEI), respectively. [18] Here, we refer to the Li lost to such reactions as inactive Li. Thus, we define Li detection techniques as having two broad goals:…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some of the Li is also lost irreversibly to side reactions at either electrode with reduced and oxidized electrolyte species on the anode (solid electrolyte interphase, SEI) and cathode (cathode electrolyte interphase, CEI), respectively. [ 18 ] Here, we refer to the Li lost to such reactions as inactive Li. Thus, we define Li detection techniques as having two broad goals: Detection of Li in the battery, separation of irreversible Li from reversible Li, and correlating it to the performance of the battery. Characterization of the irreversible Li (spatial heterogeneity or Li microstructure, morphology and chemistry once Li loss has occurred) to understand the underlying degradation mechanisms. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a more practical approach is to implement diagnostic techniques that do not necessarily require the use of a reference electrode. These include: Electrochemical Impedance Spectroscopy (EIS) [5,8,[17][18][19][20][21][22], Slow Rate Cyclic Voltammetry (SRCV) [5,8], differential voltage (dV/dQ) [15,16,[23][24][25][26] analysis, differential capacity (dQ/dV) [19,[27][28][29][30][31][32] analysis and statistical methods [33,34]. Whilst no single technique provides all the required information to decouple physical mechanisms of operation in a whole cell, their use in combination can often provide additional insight.…”
Section: Introductionmentioning
confidence: 99%
“…Here conclusions about the degradation processes occurring were alluded to by fitting the dV/dQ data to half-cell measurements of fresh electrodes. Fathi et al [23] also demonstrated the use of dV/dQ with other techniques including EIS and coulombic efficiency measurements to probe the degradation processes in Lithium Cobalt Oxide (LCO)-graphite cells.…”
Section: Introductionmentioning
confidence: 99%